Pengaruh Brand Image Dan Harga Terhadap Kepuasan Konsumen Pada Warung Soto Cahaya 99 Jatiuwung Kota Tangerang - Shumi Fitriyani; Suharni Rahayu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. The purpose of this research is to determine the effect of Brand Image and Price on customer satisfaction at Warung Soto Cahaya 99 Jatiuwung Tangerang City. The method used is quantitative. with a sampling technique using the rao purba totaling 97 respondents. Data analysis uses validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research show that brand image has a positive and significant effect on customer satisfaction with the regression equation Y = 16,632 + 0,327X1. Hypothesis testing yielded a calculate t-value > t-table or (5,386 > 1,985). So Ho is rejected and H1 is accepted, which means that there is influence between brand image and customer satisfaction at Warung Soto Cahaya 99 Jatiuwung Tangerang City. price has a positive and significant effect on customer satisfaction with the regression equation Y = 16,558 + 0,327X2. Hypothesis testing yielded a calculate t-value > t-table or (5,768 > 1,985). So Ho is rejcted and H2 is accepted, which means that there is influence between price and customer satisfaction at Warung Soto Cahaya 99 Jatiuwung Tangerang City . Brand Image and Price has a positive and significant effect on customer satisfaction with the regression equation Y = 5,557 + 0,404X1 + 0,398X2. Hypothesis testing yielded a calculated F-value > F-table or (72,164 > 3,093). This Ho is rejected and H3 is accepted. This means that there is influence between Brand Image and Price on customer satisfaction at Warung Soto Cahaya 99 Jatiuwung Tangerang City.